5x+3y=1,3x-4y=-6 by elimination method
Answers
Answered by
3
- X = -74/ 145
- y = 31 / 29
⚫️ 5x +3y = 1 ........(i)
⚫️ 3x - 4y = -6 .......( ii)
________________________
️✴️ ![\huge\bold{Given:-} \huge\bold{Given:-}](https://tex.z-dn.net/?f=%5Chuge%5Cbold%7BGiven%3A-%7D)
⚫️ 5x + 3y = 1
⚫️ 3x - 4y = -6
so,
Multiplying eq (i) with 3 and eq (ii) with 5, we get --
✴️ 15x + 9y = 1
✴ ️ 15x - 20y = -30
___________________________
so , Eliminating eq (i )and (ii), we get
15 x +9y = 1
15 x - 20y = -30
(-) (+) ( +)
_____________________________
29y = 31
y = 31 / 29
Now, putting the value of y in eq (i) ,
5x + 3y = 1
5x + 3( 31 /29) = 1
5x + 93 / 29 = 1
5x = 1 - 93 /29
5x = 29 - 93 / 29
5x = -74 / 29
x = -74 / 29 × 5
x = -74 / 145
so, the values of X and Y are-
Similar questions